Design of Ladder Climbing Assisting Device with Simple Mechanism and Safety Equipment - Fei Nging, Chang; Nik Hisyamudin Muhd Nor, (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Falling accident that caused by falling from height are happen occurly in Malaysia. Ladder climbing assisting device had been invented to reduce this type of accident. Many ladder climbing assisting device sold in the market have a big size and the mechanism of the device can be said is very complecated. This cause the maintenance job become hard and decrease the lifespan of the device. This project focuse on making a ladder climbing assisting device that have simple mechanism and in small size. In order to achieve the project objective, several research had been done by searching the related patent and existing machine. Engineering process had been applied in this project which included three phases that are conceptual design, embodiment design, and detail design. All the concept product specification are find out by using morphological chart and weight matrix evaluation. The 3D geometry layout of the final product are drawn by SolidWorks software. Finally, a final ladder climbing assisting device with simple mechanism had been design out. The machine only use 2 set of gear to complete all the mechanism. It simplified the maintenance job and increase the lifespan of the machine. In term of size, the final product have a dimension of 716mm x 307mm x 226mm with expected weight 15.82 kg. The device not only can lift people but object. In addition, a ladder stabilizer also been design out together with the machine. The ladder stabilizer help to increase the stability of the ladder.